2014
DOI: 10.1088/1468-6996/15/2/025001
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of human dermal microvascular endothelial cell and human gingival fibroblast behavior by micropatterned silica coating surfaces for zirconia dental implant applications

Abstract: Dental ceramic implants have shown superior esthetic behavior and the absence of induced allergic disorders when compared to titanium implants. Zirconia may become a potential candidate to be used as an alternative to titanium dental implants if surface modifications are introduced. In this work, bioactive micropatterned silica coatings were produced on zirconia substrates, using a combined methodology of sol–gel processing and soft lithography. The aim of the work was to compare the in vitro behavior of human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 42 publications
0
18
0
1
Order By: Relevance
“…At predetermined periods of time, the cells on FPHA were washed three times with PBS and fixed in 3.7% formaldehyde solution in PBS for 10 min at room temperature. Then 0.1% Triton-X100 PBS was added to increase cell membrane permeability, and 1% bovine serum albumin was added to reduce nonspecific background staining [23]. Finally, cells were stained with rhodamine-phalloidin 635 (Life technologies, Invitrogen, USA) for actin filaments and Hoechst 33342 (Sigma-Aldrich, USA) for nuclei.…”
Section: Methodsmentioning
confidence: 99%
“…At predetermined periods of time, the cells on FPHA were washed three times with PBS and fixed in 3.7% formaldehyde solution in PBS for 10 min at room temperature. Then 0.1% Triton-X100 PBS was added to increase cell membrane permeability, and 1% bovine serum albumin was added to reduce nonspecific background staining [23]. Finally, cells were stained with rhodamine-phalloidin 635 (Life technologies, Invitrogen, USA) for actin filaments and Hoechst 33342 (Sigma-Aldrich, USA) for nuclei.…”
Section: Methodsmentioning
confidence: 99%
“…Common strategies to achieve these goals are the modification of the roughness or the introduction of a controlled topography. For instance, micrometric silica reliefs on zirconia implant surfaces have been employed to study endothelial cells and fibroblast response in [8], where it was demonstrated that parallel grooved surfaces were able to control cells spatial distribution and to guide their growth. Also an increment in roughness has proved to be beneficial in the osseointegration of zirconia-based implants [9].…”
Section: Introductionmentioning
confidence: 99%
“…Different alternatives have been proposed to reduce bacterial adhesion to the surface of biomaterials. Among such alternatives, physical surface modifications, including roughening of zirconia surfaces [9] or modification of the topography of materials to observe cellular [10,11] or bacterial behavior [12], have received attention in the last years.…”
Section: Introductionmentioning
confidence: 99%